Analisis Pengaruh Risiko Kredit, Risiko Pasar dan Risiko Operasional Terhadap Profitabilitas pada Bank Umum BUMN yang Terdaftar di BEI Periode 2013-2020 - Nurwihda Jahrotunnupus; Gusganda Suria Manda (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to look at the influence between credit risk (NPL), market risk (NIM), and operational risk (BOPO) on Profitability (ROA) on state-owned commercial banks listed on the Indonesia Stock Exchange for the period 2013-2020. The sample used by this study is 4 state-owned banking companies. The technique for sampling used is saturated sampling. The analysis method in this study is a multiple linear regression analysis with the help of the SPSS program. The results of the study showed that together or simultaneously credit risk, market risk, and operational risks had a significant effect on profitability in state-owned commercial banks listed on the Indonesia Stock Exchange for the period 2013-2020. Partial research results on credit risk variables (NPLs) had no significant effect and had a negative relationship to profitability (ROA). The results of the study partially on market risk variables (NIM) had a significant and positive effect on profitability and the results of the study in part or partially operational risk variables (BOPO) had a significant effect and had a negative relationship to profitability (ROA) in state-owned commercial banks in the period 2013-2020.